An Exploratory Qualitative Study of Perinatal Experiences in an Acute Setting during Early Phases of the COVID-19 Pandemic - Sharon Hoosein; Pamela Winchester; Stephanie Babinski; Naomi Smith; Payalben Bhavsar; Susan Law (Patient Experience Journal)
The COVID-19 pandemic was highly disruptive for people delivering babies in-hospital and for obstetrical healthcare professionals. The purpose of this study was to explore the experiences of people with or without COVID-19 giving birth in a community-based hospital to provide patient insight to obstetrical care providers regarding the services/policies used during the pandemic. Nine interviews were conducted with participants within six months of giving birth in-hospital – four who tested positive for COVID-19 and five who tested negative. Seven themes were identified in the analysis: conflicting emotions; experiences of COVID-related protocols; altered experiences of pregnancy and birth; other aspects of in-hospital care; support from family and friends; interactions and communications with the healthcare team; and seeking information. Results were positively received by the perinatal clinical team and changes were identified to further improve experiences of care. A deeper understanding of patients' lived experiences of hospital services available during public health emergencies can offer important, actionable information for healthcare providers.